Answer:
c,d
Step-by-step explanation:
![ab^{-3x}=a(b^{-3})^x=a(\frac{1}{b^3} )^x=a[(\frac{1}{b} )^3]^x\\=a(\frac{1}{b} )^{3x}](https://tex.z-dn.net/?f=ab%5E%7B-3x%7D%3Da%28b%5E%7B-3%7D%29%5Ex%3Da%28%5Cfrac%7B1%7D%7Bb%5E3%7D%20%29%5Ex%3Da%5B%28%5Cfrac%7B1%7D%7Bb%7D%20%29%5E3%5D%5Ex%5C%5C%3Da%28%5Cfrac%7B1%7D%7Bb%7D%20%29%5E%7B3x%7D)
Answer:
x = 1
Step-by-step explanation:
Solve for x over the real numbers:
-1 + 2 + 1/x + 1/x = 3
-1 + 2 + 1/x + 1/x = 1 + 2/x:
1 + 2/x = 3
Bring 1 + 2/x together using the common denominator x:
(x + 2)/x = 3
Multiply both sides by x:
x + 2 = 3 x
Subtract 3 x + 2 from both sides:
-2 x = -2
Divide both sides by -2:
Answer: x = 1